Serum levels of prolidase and ischemia modified albumin in patients with multiple sclerosis. Issue 4 (2012) - Çevik, Mehmet Uğur; Yücel, Yavuz; Arıkanoğlu, Adalet; Varol, Sefer; Akıl, Eşref; Yüksel, Hatice; Aluçlu, Mehmet Ufuk
No abstract available